1967
DOI: 10.1007/bf01373391
|View full text |Cite
|
Sign up to set email alerts
|

A survey of urease activity in soils of Northern New South Wales

Abstract: The hydrolysis of urea to ammonia is an important pathway of conversion of organic nitrogen to inorganic nitrogen in solls receiving applications of urea 9 and excretions of urine from stock 6. Conrad 8 4 hypSthesised that urea hydrolysis could be catalysed by extracelhflar urease adsorbed in soils, a process quite independent of the catalytic action initiated by viable urease-containing soil micro-organisms. Since then the activity of this enzyme in soils has been examined both as a separate enzyme system 2 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

1985
1985
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(29 citation statements)
references
References 17 publications
1
26
0
2
Order By: Relevance
“…Burns et al [2] and Zantua and Bremner [17] found that urease activity in a soil was maintained even under anaerobic environments, high temperatures and sterile conditions. The site of urease activity has been correlated to both clay particles and soil OM [9,10,12,13,14,16]. Persistence of urease may be due to association with lignaceous organic materials and/or entrapment by clay particles which prevent decomposition and entry of microorganisms, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…Burns et al [2] and Zantua and Bremner [17] found that urease activity in a soil was maintained even under anaerobic environments, high temperatures and sterile conditions. The site of urease activity has been correlated to both clay particles and soil OM [9,10,12,13,14,16]. Persistence of urease may be due to association with lignaceous organic materials and/or entrapment by clay particles which prevent decomposition and entry of microorganisms, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…Conversely, Burns (1978) has reported that on soil samples collected on five separate occasions over a period of three years from the same location, urease activity remained the same, independent of season. McGarity and Myers (1967) reported that on soil samples collected from winter to late spring period, there were no major differences in urease activities. However, only a few studies have looked at enzyme activity in soils with several years' history of manure application (Eivazi et al, 2003;Lalande et al, 2000).…”
Section: Discussionmentioning
confidence: 96%
“…A urease foi determinada como proposto por McGarity & Myers (1967), realizando-se a incubação das amostras de solo por 3 h, a 37 °C, utilizando-se ureia 1 % como substrato, seguida de centrifugação e determinação. Os resultados foram calculados a partir de uma curva-padrão com solução de sulfato de amônio e expressos em μg N-NH 4 g -1 solo 3 h -1 .…”
Section: Análises Bioquímicas E Químicas Do Solounclassified